Cadmium‐Doped and Pincer Ligand‐Modified Gold Nanocluster for Catalytic KA2 Reaction. Issue 6 (29th December 2022) - Fan, Ji‐Qiang; Yang, Ying; Tao, Cheng‐Bo; Li, Man‐Bo
Abstract: A gold nanocluster Au17 Cd2 (PNP)2 (SR)12 (PNP=2, 6‐bis(diphenylphosphinomethyl)pyridine, SR=4‐MeOPhS) consisting of an icosahedral Au13 kernel, two Au2 CdS6 staple motifs, and two PNP pincer ligands has been designed, synthesized and well characterized. This cadmium and PNP pincer ligand co‐modified gold nanocluster showed high catalytic efficiency in the KA 2 reaction, featuring high TON, mild reaction conditions, broad substrate scope as well as catalyst recyclability. Comparison of the catalytic performance between Au17 Cd2 (PNP)2 (SR)12 and the structurally similar single cadmium (or PNP) modified gold nanoclusters demonstrates that the co‐existence of the cadmium and PNP on the surface is crucial for the high catalytic activity of the gold nanocluster. This work would be enlightening for developing efficient catalysts for cascade reactions and discovering the catalytic potential of metal nanoclusters in organic transformations. Abstract : A gold nanocluster Au17 Cd2 (PNP)2 (SR)12 with an icosahedral Au13 kernel, two PNP pincer ligands and two Au2 Cd (SR)6 staple motifs has been developed as an efficient catalyst for the KA 2 reaction. The cooperation between the three parts of the gold nanocluster has been verified as contributing to its high activity.